Realism and Social Consciousness in Premchand’s Novels: प्रेमचंद के उपन्यासों में यथार्थवाद और सामाजिक चेतना - Joshi, Kiran (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The novels of Munshi Premchand have been a powerful medium for expressing social reality in Hindi literature. Through his works, he not only portrays direct experiences of rural and urban life on the page but also reveals the voices of social inequality, exploitation, and awakening that emerge from those experiences. This study analyzes Premchand’s realistic approach and the embedded social consciousness with reference to Godan, Gaban, Karmabhumi, and Rangbhumi. Using qualitative textual analysis and contemporary critiques, the paper shows how Premchand, through his narrative art, gave literary space to rural economic relations, caste inequality, the condition of women, and nationalist consciousness. As a result, it becomes clear that Premchand’s writings are not only historical documents but also provide relevant guidance for today’s social discourse. Abstract in Hindi Language: मुंशी प्रेमचंद के उपन्यास हिन्दी साहित्य में सामाजिक यथार्थ को व्यक्त करने का एक प्रबल माध्यम रहे हैं। वे अपनी रचनाओं के माध्यम से न केवल ग्रामीण एवं नगरीय जीवन के प्रत्यक्ष अनुभवों को पन्नों पर उतारते हैं, बल्कि उन अनुभवों से उत्पन्न सामाजिक असमानताओं, शोषण और चेतना के स्वर को भी उद्घाटित करते हैं। यह अध्ययन गोदान, गबन, कर्मभूमि तथा रंगभूमि के सन्दर्भ में प्रेमचंद के यथार्थवादी उपागम और उनमें निहित सामाजिक चेतना का विश्लेषण प्रस्तुत करता है। गुणात्मक पाठ्य-विश्लेषण और समकालीन आलोचनाओं के सहारे यह लेख दिखाता है कि प्रेमचंद ने कथा-कला के माध्यम से किस प्रकार ग्राम्य अर्थ-सम्बन्ध, जातिगत असमानता, नारी-स्थिति तथा राष्ट्रवादी चेतना को साहित्यिक विमर्श में स्थान दिया। नतीजतन यह स्पष्ट होता है कि प्रेमचंद की रचनाएँ न सिर्फ़ ऐतिहासिक दस्तावेज़ हैं, बल्कि आज के सामाजिक विमर्श के लिए भी प्रासंगिक निर्देश प्रदान करती हैं। Keywords: प्रेमचंद, यथार्थवाद, सामाजिक चेतना, गोदान, गबन, जातिवाद, राष्ट्रवाद, स्वतंत्रता आंदोलन।